The Effects of Unripe Pawpaw Seeds (Carica Papaya) Extract on the Histology of the Testis of Guinea Pigs (Journal of Experimental and Clinical Anatomy, 2004)
The antifertility effect of unripe paw-paw seeds (Carica papaya) on the testes of adult male guinea pigs was studied. Oral doses of the unripe paw-paw seeds extract at 220mg/kg bodyweight, 330mg/kg body weight and 44mg/kg body weight were administered orally for 7 days. Histological observation at low dose of 220mg/kg showed reduction in the interstitium and in the numbers of spermatozoa in the lumen of the tubule. At high dose of 440mg/kg body weight, there was degeneration of the basement membrane of the tubules, erosion of the interstitium and degeneration of tails of the spermatozoa in the lumen of the tubule. Our results suggest that unripe pawpaw seeds extract is cytotoxic to the testes of adult male guineapigs and may cause oligospermia in these animals.